Kinerja pustakawan perpustakaan perguruan tinggi Islam di Provinsi Bengkulu - Rhoni Rodin (Universitas Padjadjaran, 2018)
In the present era of digital information, academic library professionals are required to perform creatively and innovatively. The purpose of this study was to explore and analyze the performance of academic librarians in fostering creativity and innovation in the digital era. This study used the descriptive qualitative method. Data were obtained through interviews and documentation, while the data analysis was conducted using the qualitative inductive approach. The results showed that university librarians carried some performances in fostering creativity and innovation in the present digital era. First, librarians carried out application-based library automation that was carried out to facilitate library services. Second, librarians created a library website. This website was needed to strengthen the position of the library in the digital era. Third, librarians made the library journal as a place to express their thoughts in the field of libraries and librarianship and even created an Online Journal System (OJS). Fourth, some librarians were able to show their existence by becoming resource persons or presenters in scientific activities in the field of libraries and librarianship. Fifth, librarians were able to implement e-libraries in both e-books and e-journals. This e-library would undoubtedly make it user easier for the user to access information because it was not limited to space and time. In conclusion, the digital era facilitates easy access and use of digital-based information. The librarian's creativity and innovation in this present digital era are needed to improve the librarian performance.